Notes on the Bankruptcy Problem: an Application of Hydraulic Rationing - Tamás Fleiner; Balázs Sziklai (Hungarian Academy of Sciences, Institute of Economics, 2011)
We offer a new approach to the well-known bankruptcy problem based on Kaminski's idea. With the help of hydraulic rationing we give a proof to Aumann and Maschlers theorem i.e. the consistent solution of a bankruptcy problem is the nucleolus of the corresponding game. We use a system of vessels and water and the principles of mechanics to show this fact. The proof is not just simple and demonstrative but also provides an insight how the nucleolus is constructed in such games.
Keywords: C71; 330; bankruptcy problem; nucleolus; hydraulic rationing; Insolvenz; Ungleichgewichtsökonomie; Core; Kooperatives Spiel; Theorie